Memorable tourism experience at smart tourism destinations: Do travelers' residential tourism clusters matter?. (March 2023) - Shin, Hyejo Hailey; Kim, Jinwon; Jeong, Miyoung
Abstract: Despite strong evidence from the social ecological model suggesting the influences of the residential built environment on individuals' behaviors, the effects of travelers' residential tourism clusters on their tourism experience at smart tourism destinations have not been investigated. Thus, this study aims to understand the effects of travelers' residential tourism clusters on their memorable tourism experience at a smart tourism destination. To achieve the purpose, this study investigated (1) how various tourism products influence travelers' memorable experiences and future behavioral intentions, and (2) the moderating effect of travelers' residential tourism clusters in the proposed relationships. Findings showed the positive effects of tourism resources and smart tourism technologies' interactivity and personalization on memorable tourism experience, and the group difference between travelers from more-tourism clustered and less-tourism clustered areas. These findings can help tourism scholars and practitioners understand the effects of both destination-related attributes and traveler-related attributes on travelers' memorable experience at smart tourism destinations. Highlights: The impacts of various tourism products on memorable experience were examined. We identified how travelers' residential tourism clusters affected traveler behavior. We investigated various smart tourism destination attributes on memorable experience. We found how travelers' residential tourism clusters affected memorable experience. The effect of memorable experience was stronger for travelers from more-clustered areas.